Labor market affiliation after deployment: Danish soldiers fare well, but face increased risk of long-term sickness absence when returning from Afghanistan - Andreas Elrond; Christian Stoltenberg; Lars Nissen; Anni Nielsen; Jacob Pedersen (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: Little is known about the employment prospects of formerly deployed soldiers (FDS) after returning from military deployment. The few studies that exist reported mixed results, and even fewer undertook comparisons with a civilian control population. This study compared labor market transitions of FDS within five years of returning from their first international deployment with those of a closely matched general-population control group. METHODS: Danish FDS (N=6653) returning from their first ever peacekeeping in Kosovo or Iraq, or more intense combat in Afghanistan (period 2002-2012), were matched with non-deployed controls from the general population (N=62 281). We modelled time-to-event using Cox models, for transitioning from employed to unemployed and back, and from work to long-term sickness absence and back. Each analysis adjusted for age and level of education and was stratified for the region of residence and the underlying period. RESULTS: Independent of deployment country, FDS had a lower risk of becoming unemployed [hazard ratio (HR) 0.55-0.73] and a higher chance of obtaining employment (HR 1.19-1.31) than matched controls. FDS returning from Afghanistan had a higher risk of long-term sickness absence (HR 1.66), while those returning from Kosovo had a higher chance of returning to work (HR 1.24). CONCLUSION: Independent of deployment country, FDS fared better in the labor market within five years of returning home compared to non-deployed controls. However, deployment to Afghanistan was related to a higher risk of long-term sickness absence, suggesting that some soldiers have worse outcomes than the general population.